Data‐driven enzyme immobilisation: a case study using DNA to immobilise galactose oxidase. Issue 3 (27th November 2020) - Ott, Wolfgang; Ceccarelli, Alessandro; Manning, Jack; Turner, Nicholas J.; Oppenheimer, Robert
Abstract : Biocatalysis has the potential to enable green chemistry. New methods of enzyme immobilisation will be required to improve enzyme stability, product purification, and compatibility of different enzymes in the same reaction conditions. Deoxyribonucleic acid (DNA) stands out among supramolecular scaffolds, as simple Watson–Crick base‐pairing rules can be used to rationally design a unique nanoscale environment around each individual enzyme in a cascade. Enhancements of enzyme activity and stability on DNA nanostructures have previously been reported, but never in the context of industrially relevant chemical syntheses or reaction conditions. Here, the authors show DNA can enhance the activity and stability of a galactose oxidase mutant, which could be used in a cascade to produce bioplastics from lignin. The enzyme was enhanced in the cell‐free extract, which to their knowledge has not been shown before for any enzymes on DNA. This is significant because crude biocatalytic reactions are vastly more cost‐effective. This opens the door to further work on multienzyme cascades by tuning the properties of individual enzymes.